(untitled) (Research, Society and Development, 2021)
Urbanization is essential to the population’s quality of life, but positive and negative environmental impacts always accompany it. The objective of this research was to evaluate the environmental impacts caused in the neighborhood Maracanã, Santarém, Pará. The method applied was photo-analytical research, with a quantitative and qualitative scope, and applied nature. The primary data obtained on-site, via photographs, and the secondary in open-access academic links to select the works of literature published between 2012 and 2021, with only one pioneer literature (1994). The data obtained and analyzed were allocated in a matrix adapted from Leopold, where the calculations of magnitude and importance of each of the three environmental media made due to ongoing operations in this neighborhood: earthworks, excavation, and asphalt paving. For the physical environment, the least impacted (-197), identified that the soil environmental element is undergoing a compaction process (0.9). The anthropic element (-4) is the most impacted of the three analyzed environments. Of the 30 environmental components measured, the job offer presented the highest impact from the family income (-2). Because of these data, corrective mitigation measures suggested as a matter of urgency to avoid more considerable damage to the community and the environment, that is, in the Maracanã neighborhood.